Branching Structures of Alkali Metal Ion Responsive Supramolecules Based on Symmetric Structures of N,N-Bis(5-alkyl-2-hydroxybenzyl)methylamine - Kaewvilai, Attaphon; Rungsimanon, Thitiporn; Koonsaeng, Nattamon; Chirachanchai, Suwabun; Laobuthee, Apirat (Asian Journal of Chemistry, 2010)
This work aimed to design and synthesize the alkali metal responsive supramolecules based on symmetric structures of N,N-bis(5-alkyl-2-hydroxybenzyl)methylamine. Novel branching structures of products, such as, N,N-bis-[5-methyl-2-(1’,3’-diethoxy-2’-propoxy) benzyl]methylamine (P-I), N,N-bis-[5-ethyl-2-(1’,3’-diethoxy-2’-propoxy)benzyl]methyl amine (P-II) and N,N-bis- [5-methoxy-2-(1’,3’-diethoxy-2’-propoxy)benzyl]methylamine (P-III) were successfully prepared. The alkali metal ion extraction efficiency of products was studied by Pedersen’s technique. The stoichiometric interaction ratios of host compounds (P-I to P-III) with alkali metal ion guests determined by UV-visible, 1H NMR and ESI-MS spectroscopic techniques were found to be 2:1, 3:1 and 4:1, respectively.